Proprioceptive Disturbance in Chronic Neck Pain: Discriminate Validity and Reliability of Performance of the Clinical Cervical Movement Sense Test - Röijezon, Ulrik; Jull, Gwendolen; Blandford, Christian; Daniels, Anna; Michaelson, Peter; Karvelis, Petros; Treleaven, Julia (Frontiers in Pain Research, 2022)
Chronic neck pain is associated with sensorimotor dysfunctions which may affect symptoms, daily activities and prevent recovery. Feasible, reliable and valid objective methods for assessment of sensorimotor functions are important to identify movement impairments and guide interventions. The aim was to investigate discriminative validity of a clinical cervical movement sense test, using a laser pointer and an automatic video-based scoring system. Individuals with chronic neck pain of idiopathic onset (INP), traumatic onset (TNP) and healthy controls (CON) were tested. Associations between movement sense and neck disability were examined and the repeatability of the test was investigated. A total of 106 participants (26 INP, 28 TNP and 52 CON) were included in a cross-sectional study. Acuity, Speed, Time and NormAcuity (i.e., normalized acuity by dividing acuity with movement time) were used as outcome measures. ANOVAs were used for group comparisons, and Pearson correlations for associations between movement sense variables and neck disability (NDI). Sixty of the participants (30 CON, 17 INP and 13 TNP) performed the test at a second occasion to explore test- retest reliability. Results revealed a reduced NormAcuity for both INP and TNP compared to CON (p<0.05). The neck pain groups had similar Acuity but longer Time compared to CON. Among TNP there was a fair positive correlation between Acuity and NDI, while there was a negative correlation between Acuity and NDI among INP. Reliability measures showed good to excellent ICC values between tests, but standard error of measurements (SEM) and minimal detectable change (MDC) scores were high. The results showed that NormAcuity is a valuable measure to identify disturbed cervical movement sense among INP and TNP. While Acuity was similar between groups different strategies were used, such as longer Time to perform the task among neck patient groups. Few differences were identified between the neck pain groups but altered strategies may exist. Reliability was acceptable and the test is feasible to perform in the clinic. However, the technical complexity of the automated image analysis is a concern. Future developments will provide more feasible solutions.